Maternal mortality in Lao People's Democratic Republic - Estudillo, Jonna (The Philippine Review of Business and Economics, 2018)
Lao People?s Democratic Republic (PDR) has the highest maternity mortality ratio (MMR- deaths per 1,000 live births) in Southeast Asia. This essay identifies the reasons for the high but declining MMR in the country. MMR remains high because of the high inequality in the uptake of critical maternal health services. The least advantaged women have lagged behind the most advantaged in terms of ante-natal care and delivery care. The decline in MMR could be attributed to various government social health protection programs that eased the financial constraint posed by the high out-of-pocket payments in maternal health care.